The Barriers And Challenges Of Women’s Involvement In The Construction Industry Within Klang Valley Area - Khairul Firdaus, Anuar; Dk. Siti Suhailah, Pg. Haji Abas; Azian, Ibrahim; Azi Izwani, Nor Hamzah (Penerbit Universiti Malaysia Pahang, 2017)
Construction industry has been viewed as a “male only image” industry and is associated with the need of physical strength, adjustments to harsh outdoor working conditions and oppressive dialects. Fortunately, throughout the years, women are seen to be involved in construction industry. However, women involved in construction industry still face barriers and challenges. The objectives of this research are to examine the ideal characteristics and attributes of women involved in the construction industry, to identify the major barriers and challenges faced by women involved in the construction industry and to recommend company policies which can be adopt to enhance women involvement in construction industry. The methodology adopted to carry out this research was quantitative method via questionnaire survey. Convenience sampling was used, whereby respondents who have experienced in construction industry were randomly selected. The results concluded that the top three ideal characteristics and attributes of women involved in construction industry are to show self-confidence, while remaining the feminine characteristics, research and alliance. For barriers, the major barriers are private life demands, family commitment, work environment, sexual harassment and flexible working hour. Lastly, it can be concluded that major challenges come from women‟s support system and the women itself. Additionally, three recommended policies were identified namely working hour, welfare and outstation. It is hope that this research paper will provide useful information on future to all parties involved especially women in construction industry as well.